EXPERIMENTAL STUDY ANALYSIS OF DISC HARROWS FOR SURFACE TREATMENT OF ROW CROPS - O.Mamadiyorov, N.Saidov, M.Xidirov, D.B.Irgashev (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Corn production generates a signifcant amount of residue and corn residue itself is slow in decomposition, which results in accumulated residue remaining in the feld. Tis can cause equipment plugging and poor soil-seed contact for seeding operations, which would negatively afect plant emergence and ultimately crop yield. Modern harvesters use adapters to chop and crush the residue. For situations where adapters are not available, it is necessary to employ tillage operation to break up the residue and mix it with soil for faster decomposition. Furthermore, feld studies have shown that incorporating corn residue into the soil increased the thousand-kernel weight, grain yields, and nitrogen efciency of the following crop as compared to tillage treatments without residue biomass return. Vertical tillage (VT), a newly coined form of tillage practice, can deal with high amount of crop residue in a sustainable manner.